Is a Mechanic Prosthetic Valve in Tricuspid Position an Absolute Impediment to Implant a Definitive Electrode in the Right Ventricle? - Arabia, Luis Antonio; Luciano, Juan Carlos (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
This is the case of a middle-aged woman with Ebstein anomaly, who had a tricuspid valve replacement with a mechanic Starr-Edwards caged-ball valve many years ago, and needed an implantable cardioverter defibrillator (ICD) and ventricular pacing due to ventricular tachycardia and atrioventricular block with syncope. Furthermore, she has a chronic respiratory disease that make open chest surgery inadvisable. Prosthetic valves are a real obstacle to cross them and place catheters in the distal chamber. This report shows a technique to get access to the right ventricle endocardium through the annulus and placing the ICD electrode with correct sensing and pacing.